Respostas
respondido por:
1
-6x²+x+1
delta=b²-4.a.c
delta=1²-4.(-6)+1
delta=1+24
delta= 25
-b+-raiz de delta/2.a
-1+-raiz de 25/2.(-6)
-1+-5/-12
x'=-1-5/-12= 0,5
x''=-1+5/-12= 0,3
y=-6.0,5+0,3+1
y=7,8
delta=b²-4.a.c
delta=1²-4.(-6)+1
delta=1+24
delta= 25
-b+-raiz de delta/2.a
-1+-raiz de 25/2.(-6)
-1+-5/-12
x'=-1-5/-12= 0,5
x''=-1+5/-12= 0,3
y=-6.0,5+0,3+1
y=7,8
danyellecosta:
obrigado :)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás